Error Analysis of Stonex X300 Laser Scanner Close-range Measurements - Abed, Fanar M.; Jasim, Luma K.; Bori, Marwa M. (Geomatics and Environmental Engineering, 2024)
This research reports an error analysis of close-range measurements from a Stonex X300 laser scanner in order to address range uncertainty behavior based on indoor experiments under fixed environmental conditions. The analysis includes procedures for estimating the precision and accuracy of the observational errors estimated from the Stonex X300 observations and conducted at intervals of 5 m within a range of 5 to 30 m. The laser 3D point cloud data of the individual scans is analyzed following a roughness analysis prior to the implementation of a Levenberg–Marquardt iterative closest points (LM-ICP) registration. This leads to identifying the level of roughness that was encountered due to the range-finder’s limitations in close-ranging as well as measurements that were obtained from extreme incident angle signals. The measurements were processed using a statistical outlier removal (SOR) filter to reduce the noise impact toward a smoother data set. The geometric differences and the RMSE values in the 3D coordinate directions were computed and analyzed, which showed the potential of the Stonex X300 measurements in close-ranging following a careful statistical analysis. It was found that the error differences in the vertical direction had a consistent behavior when the range increased, whereas the errors in the horizontal direction varied. However, it is more common to produce errors in the vertical direction as compared to the horizontal one.